Reforming the personal income tax system in the Peoples Republic of China. (Observations and Suggestions, 2020)
This publication outlines personal income tax system reforms in the Peoples Republic of China (PRC) following the amendment of the countrys Personal Income Tax Law in 2018.The PRC has made significant steps in amending the countrys Personal Income Tax Law in 2018. Yet, there are still issues to consider for further improvement. Based on international experiences and comparisons, this publication recommends that personal income tax system reforms in the PRC must include (i) broadening the countrys tax base, (ii) streamlining and limiting special deductions, (iii) optimizing the tax rate structure, and (iv) reinforcing tax collection and administration by strengthening compliance and improving law enforcement.